Quartzo ametista nos ambientes vulcano-basáltico, granito-pegmatítico e quartzo-hidrotermal: geologia, mineralogia e gênese dos depósitos em Minas Gerais - Coralie Heinis Dias (2020)
In Minas Gerais State, amethyst quartz deposits occur associated to three different geological environments: (1) cavities within basalts (geodes) of the Serra Geral Formation, in Triângulo Mineiro region; (2) pegmatites from the Eastern Brazilian Pegmatite Province, at northeast of the State, and; (3) hydrothermal quartz veins, such as those associated to the Espinhaço Mountain Range and vicinities. In order to investigate mineralogical and genetic differences in amethyst from environments cited above, amethyst deposits and occurrences were studied in each one of the geologic environments. Geochemical analyses on basalts from the Serra Geral Formation indicated that such rocks have high titanium content and low volatiles. They also revealed chemical similarity to the host rocks of the world class deposits present at Rio Grande do Sul State, although those latter have higher volatiles contents. Amethyst deposits in pegmatite from Minas Gerais have not been exactly localized, so one occurrence from Pancas (Espírito Santo State), close to the boundary of Minas Gerais State, was studied. The deposits located in Espinhaço Supergroup unities are those from Grão Mogol and Buenópolis. In the vicinities, the deposit from Felício dos Santos is inserted in Macaúbas Group unities, whereas the Montezuma Mine occur within the context of the Santo Onofre Group. In order to obtain data relative to the crystallization conditions of this mineral in that different genetic environments, fluid inclusion studies including petrography and microtermometry have been conducted in amethyst samples from some of those localities. Amethysts from basalt cavities showed only aqueous one-phase inclusions, suggesting a low temperature formation environment. With respect to amethyst from hydrothermal veins and pegmatite, fluid inclusions can be either aqueous one-phase, aqueous two-phase, aquocarbonic three-phase or aqueous three-phase, with halite. The carbonic composition of the system H2O-CO2- NaCl was confirmed by Raman spectroscopy analyses, and suggests metamorphic or magmatic source for the fluids. Samples from hydrothermal veins show salinity values varying from 2,4 to 9,7 wt.% NaCl equivalent, representing low to moderate salinity fluids. Based on homogenization temperatures obtained during heating experiments, at least two generations of fluids were considered in these samples. The first one showed minimum trapping temperatures between 249° C and 391°, and the second registered temperatures between 82°C and 203°C. Fluid inclusions trapped in amethyst from a pegmatite body have moderate salinity with most values lying between 15 and 25 wt.% NaCl equivalent, reflecting elevated salt content in pegmatite forming fluids. Two different fluid gengerations were also interpreted, with the first one showing minimum trapping temperatures between 268° C and 375° C and the second from 125°C to 247°C. Amethyst from both hydrothermal vein and pegmatite environments show hematite solid inclusions, indicating that mineralizing fluid was Fe-rich and hence suggesting a possible magmatic origin for the fluid. In order to contribute to the understanding of amethyst causes of color, analytical studies of natural samples as well as gamma ray irradiated and heat-treated samples were conducted using optical absorption and electron paramagnetic resonance (EPR) techniques. From optical absorption analyses, it was observed that heating eliminates or attenuates bands initially present close to 375 and 530 nm, and irradiation restores or intensifies such bands, related to amethyst color centers. EPR analyses showed that irradiation eliminates several signals attributed to centers related to Fe3+ impurities, and reinforces an isotropic signal close to 340 mT, especially in samples which acquired darker violet color. After heating at 450° C, signals close to 340 mT disappear. Changes in signals after treatments conducted in amethyst samples may be related to the conversion of Fe3+ ions into Fe4+ ones, resulting in amethyst color acquisition or disappearance.